2020
DOI: 10.1186/s13063-020-4050-8
|View full text |Cite
|
Sign up to set email alerts
|

Doll therapy intervention for women with dementia living in nursing homes: a randomized single-blind controlled trial protocol

Abstract: Background: Doll therapy is a non-pharmacological intervention for people with dementia aimed to reduce distressing behaviours. Reliable results on the efficacy of Doll therapy for people with dementia are needed. The concept of attachment theorised by Bowlby has been proposed to explain the Doll therapy process, but it has not been proven to influence the response to doll presentation. Methods/design: This single-blind, randomised controlled trial will involve people with dementia living in nursing homes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In addition, it has been suggested that such a surrogate for a real infant can revive the positive emotions of the parent-child relationship, 19 and that the lullabies, feeding, holding, and singing activities carried out for the sake of the "baby" can increase self-esteem. 24,25 Furthermore, it has been reported that doll therapy creates a therapeutic bond, 9,26 promotes feelings of calmness and competence, provides sensory stimulation, and contributes to the development of communication with the patient's external environment and caregivers. 18,11,24,25 Studies in the literature have demonstrated similar results, 9,11,16,17,27 and it has been reported that doll therapy has conferred positive effects on behavioral, psychological, emotional, and cognitive problems, as well as the social lives of institutionalized patients with severe dementia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been suggested that such a surrogate for a real infant can revive the positive emotions of the parent-child relationship, 19 and that the lullabies, feeding, holding, and singing activities carried out for the sake of the "baby" can increase self-esteem. 24,25 Furthermore, it has been reported that doll therapy creates a therapeutic bond, 9,26 promotes feelings of calmness and competence, provides sensory stimulation, and contributes to the development of communication with the patient's external environment and caregivers. 18,11,24,25 Studies in the literature have demonstrated similar results, 9,11,16,17,27 and it has been reported that doll therapy has conferred positive effects on behavioral, psychological, emotional, and cognitive problems, as well as the social lives of institutionalized patients with severe dementia.…”
Section: Introductionmentioning
confidence: 99%
“…DTI offers relevant advantages in terms of costs-effectiveness: unlike other nonpharmacological treatments (e.g., pets, music, or art therapy), it does not necessarily require the presence of a skilled therapist but can be carried out within 24 h by nursing home staff (nurses, assistants) if they are properly trained and supervised. As previously described [ 7 , 29 ], PWD take care of the dolls even in the absence of a professional caregiver.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention procedure has been described in detail elsewhere [ 29 ]. Participants attended daily DTI or SI sessions for a maximum of one hour, led by a trained professional caregiver.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation